Proceedings of the 2018 ACM Symposium on Eye Tracking Research &Amp; Applications 2018
DOI: 10.1145/3204493.3204569
|View full text |Cite
|
Sign up to set email alerts
|

Hidden pursuits

Abstract: Figure 1: We explore HiddenPursuits, where the trajectory of a moving target is partially hidden while users perform selections via smooth pursuit eye movements. This allows (1) expanding selection areas by enabling targets to move out of the bounds of small displays (e.g., mobile devices and smartwatches), and (2) selection of targets even if they are partially occluded (e.g., in VR). In our user study, we hid 0%, 25%, 50% and 75% of the target's (fish) trajectories, and measured how well eye movements correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Related work has developed and studied a variety of technical implementations of motion matching interaction, using webcams [11,12], depth-sensors [9], eye-trackers [18,25,37,48,52], magnets [39], and inertial measurement units (IMUs) embedded in smart-watches [50], phones [4], and AR headsets [19]. These implementations are supplemented with work on further algorithmic developments and novel deployments [10,16,21,27,29,47]. Taken together, these laboratory studies have shown that people are able to accurately interact with motion matching interfaces after a very short learning period.…”
Section: Introductionmentioning
confidence: 99%
“…Related work has developed and studied a variety of technical implementations of motion matching interaction, using webcams [11,12], depth-sensors [9], eye-trackers [18,25,37,48,52], magnets [39], and inertial measurement units (IMUs) embedded in smart-watches [50], phones [4], and AR headsets [19]. These implementations are supplemented with work on further algorithmic developments and novel deployments [10,16,21,27,29,47]. Taken together, these laboratory studies have shown that people are able to accurately interact with motion matching interfaces after a very short learning period.…”
Section: Introductionmentioning
confidence: 99%